PERBANDINGAN PENGGUNAAN BAHAN BAKAR DAN NILAI TAMBAH INDUSTRI TEMPE PENGGUNA KAYU BAKAR - Insusanty, Enny; Azwin, Azwin; Sadjati, Emy (Wahana Forestra: Jurnal Kehutanan, 2016)
This study aims to determine the use of various fuels and value -added soybean industry users of firewood. Experimental research method is to determine the time and the volume of a variety of fuels . To obtain data on value -added soybean industry firewood users do method survey conducted to tempe entrepreneurs with purposive sampling method.Based on data from the fuel use of the most efficient cooking time to enter into the boiling water experiment is the same volume that is 2 liters of data is obtained using the gas. LPG has a high thermal energy by combustion fuel for 7 minutes with a volume of 0.054 kg of fuel chart . Then followed with the use of kerosene to take 10 minutes and liters of fuel for boiling water 0,01. Fire resulting from green kerosene a little sooty issued. Meanwhile, firewood and wood pellets takes 15 minutes with a volume of 2 kg of fuel.Value of the average profit businesses tempeh is Rp 290,000 per sack (50 kg), which according to tempe entrepreneurs already minimal profit because of the high price of soybeans is currently through the price of Rp 450,000 / sack . With the price of Rp 9.000/kg obtained soybean processing industry added value of Rp 9000/kg soybean tempeh, profit Rp7.500/kg soybean, margin Rp 11.000/kg soybeans, and other inputs Rp 2000/kg ( 18.18 %) were include wood fuel input of Rp 500/kg soybean or 4.5 %.